2010
DOI: 10.1136/adc.2009.165183
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for neonates with enterovirus myocarditis

Abstract: EV myocarditis is a rare but severe disease in the neonatal period, which often leads to death or results in serious chronic cardiac sequelae like chronic heart failure, aneurysm formation within the left ventricle and mitral regurgitation. Chronic cardiac drug therapy is necessary in the majority of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 34 publications
0
71
0
2
Order By: Relevance
“…Event-free survival for all-cause viral myocarditis is reported to be 72–89% at 1 year17–19 30 31 and 63–74% at 5 years 17–19. PVB19 myocarditis has similar mortality to neonatal enterovirus myocarditis, but the recovery of cardiac function appears better 32. Overall, it seems that the outcome of PVB19 myocarditis is worse than all-cause viral myocarditis and in our series, recovery is slower.…”
Section: Discussionmentioning
confidence: 48%
“…Event-free survival for all-cause viral myocarditis is reported to be 72–89% at 1 year17–19 30 31 and 63–74% at 5 years 17–19. PVB19 myocarditis has similar mortality to neonatal enterovirus myocarditis, but the recovery of cardiac function appears better 32. Overall, it seems that the outcome of PVB19 myocarditis is worse than all-cause viral myocarditis and in our series, recovery is slower.…”
Section: Discussionmentioning
confidence: 48%
“…In the case series studied by Freund et al ,6 all of the survivors developed dilated cardiomyopathy and only 28% of previously reported patients, who were managed mainly conservatively, demonstrated a return to normal ventricular function. All three of our survivors had a favourable cardiac outcome demonstrated by normal echocardiographic findings at last follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…The survival rate in the current study is 43% and is comparable to the 34% survival in the 35 previously reported cases of patients supported with ECMO. On the other hand, overall survival of 35 patients with EV myocarditis summarised in a review of the literature by Freund et al 6 was 59%. Only four of these patients required ECMO, and thus most of the survivors might have had a milder form of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…Most cases of HNC present within the first week of life and are characterized by serum transaminase levels 3-times greater than the normal value for age, thrombocytopenia (<100 × 10 9 /L), prolonged prothrombin time and/or evidence of hepatic necrosis or extensive coagulopathy. A review of reported cases by Freund et al 9 described that myocarditis due to neonatal enterovirus infection was associated with a mortality rate of 31%, and severe cardiac damage in two-thirds of cases. 3 Our patient's clinical course was fulminant, and she required aggressive cardiorespiratory support and renal-replacement therapy.…”
Section: Discussionmentioning
confidence: 99%